Deradikalisasi Agama melalui Internalisasi Nilai Moderasi Beragama: Studi pada Kementerian Agama Kota Cirebon - Muhammad Syahrul Azzahra (Journal of Religion and Social Transformation, 2024)
Religious radicalism in Indonesia has emerged as an urgent issue in recent years, influenced by various political, social, economic, and religious factors. Although Indonesia is known for its diversity, the increase in radical activities is highly concerning. Key factors contributing to the spread of radicalism include political instability, social conflict, economic inequality, and religious extremism. The rapid dissemination of radical ideologies through social media and the internet further exacerbates the problem. Cirebon, a city in West Java, mirrors national trends with its own specific challenges. Political dissatisfaction, economic disparity, and radical religious teachings contribute to this issue. The Ministry of Religious Affairs (Kemenag) in Cirebon plays a crucial role in carrying out religious deradicalization through programs that promote moderation and religious tolerance. Kemenag's initiatives include interfaith dialogue, religious education reform, and close collaboration with law enforcement. These efforts aim to counter radical influences and foster a peaceful and diverse society. Despite the challenges, Kemenag's proactive measures and local-global collaboration are essential in mitigating the impacts of radicalism, ensuring security, and promoting social stability.